THE IMPLEMENTATION OF KAHOOT IN TEACHING READING COMPREHENSION AT ELEVENTH GRADE OF SMK TEKNOLOGI YPL LIRIK - Putri Febrianti; Destri Wahyuningsih (J-Shelves of Indragiri (JSI), 2026)
The rapid advancement of educational technology has significantly transformed English language teaching, particularly in the domain of reading comprehension. This study investigates the implementation of Kahoot, an interactive game-based learning platform, in teaching reading comprehension to eleventh-grade students at SMK Teknologi YPL Lirik. Reading comprehension remains one of the most challenging skills for Indonesian EFL learners, often due to limited vocabulary, lack of motivation, and passive learning environments. Kahoot offers a dynamic alternative by integrating gamification elements into classroom instruction. The purpose of this study is to describe and analyze how Kahoot is implemented in teaching reading comprehension, as well as to explore students' responses and teachers' challenges in its application. This research employs a qualitative descriptive method, with data collected through classroom observation, in-depth interviews with the English teacher, and questionnaires distributed to the students. The findings reveal that Kahoot is implemented in three main stages: pre-activity, whilst-activity, and post-activity. During implementation, students demonstrated increased engagement, enthusiasm, and active participation compared to conventional learning settings. The competitive and collaborative features of Kahoot contributed to students' motivation to read and understand texts more carefully. However, several challenges were identified, including internet connectivity issues, device availability, and the need for adequate preparation time from the teacher. The study concludes that Kahoot is an effective supplementary tool in reading comprehension instruction when supported by adequate technological infrastructure and proper pedagogical planning.